Expression Profiling Using a cDNA Array and Immunohistochemistry for the Extracellular Matrix Genes FN-1, ITGA-3, ITGB-5, MMP-2, and MMP-9 in Colorectal Carcinoma Progression and Dissemination - Suzana Angelica Silva Lustosa; Luciano de Souza Viana; Renato José Affonso; Sandra Regina Morini Silva; Marcos Vinicius Araujo Denadai; Silvia Regina Caminada de Toledo; Indhira Dias Oliveira; Delcio Matos (The Scientific World Journal)
Colorectal cancer dissemination depends on extracellular matrix genes related to remodeling and degradation of the matrix structure. This investigation intended to evaluate the association between FN-1, ITGA-3, ITGB-5, MMP-2, and MMP-9 gene and protein expression levels in tumor tissue with clinical and histopathological neoplastic parameters of cancer dissemination. The expression associations between ECM molecules and selected epithelial markers EGFR, VEGF, Bcl2, P53, and KI-67 have also been examined in 114 patients with colorectal cancer who underwent primary tumor resection. Quantitative real-time PCR and immunohistochemistry tissue microarray methods were performed in samples from the primary tumors. The gene expression results showed that the ITGA-3 and ITGB-5 genes were overexpressed in tumors with lymph node and distant metastasis (III/IV-stage tumors compared with I/II tumors). The MMP-2 gene showed significant overexpression in mucinous type tumors, and MMP-9 was overexpressed in villous adenocarcinoma histologic type tumors. The ECM genes MMP9 and ITGA-3 have shown a significant expression correlation with EGFR epithelial marker. The overexpression of the matrix extracellular genes ITGA-3 and ITGB-5 is associated with advanced stage tumors, and the genes MMP-2 and MMP-9 are overexpressed in mucinous and villous adenocarcinoma type tumors, respectively. The epithelial marker EGFR overactivity has been shown to be associated with the ECM genes MMP-9 and ITGA-3 expression.